THE DEVELOPMENT OF DECISION SUPPORTING SYSTEM FOR EMPLOYEE’S WORK EVALUATION FOR POSITION PROMOTION BY USING AHP (ANALYTICAL HIERARCHY PROCESS) AND WP (WEIGHTED PRODUCT) METHOD CASE STUDY AT THE SAMAYA UBUD BALI HOTEL - Wisma Yasa, I Made (Universitas Pendidikan Ganesha, 2012)
This study is a case study which took place at The Samaya Ubud Bali Hotel. Theaims of this study are: (1) to design a decision supporting system for employee’s workevaluation for position promotion by using AHP (Analytical Hierarchy Process) andWP (Weighted Product) method, (2) to implement a decision supporting system foremployee’s work evaluation for position promotion by using AHP (AnalyticalHierarchy Process) and WP (Weighted Product) method. In designing andimplementing of the program, researcher used 2 main methods namely AHP (AnalyticalHierarchy Process) and WP (Weighted Product) in which those two methods belong toMADM (Multi Attribute Decision Making). The inputs of this application are criteriadata, criteria comparison scale, and employees’ score data. On the other hand, theoutput is in form of information that shows the employee’s rank. Trial was done tocheck the agreeability of the employee’s final score calculated by the system with thefinal score calculated manually. In this step, the hotel contribution was required todetermine and process the employees’ final score.In designing and implementing the application design, waterfall method which iswell known as classic life cycle model was used. This waterfall model is a classic modelwhich is systematically able to build software. This model involves some steps whichare: (1) requirements definition, (2) system and software design, (3) implementation andunit testing and (4) integration and system testing.The implementation and the trial of this system used Embarcadero Delphi 2010.From the trial it was found that the data produced by the system was already appropriatewith the data calculated manually. Base on this result, this decision supporting systemfor employee’s work evaluation for position promotion by using AHP (AnalyticalHierarchy Process) and WP (Weighted Product) method was already suitable with theAHP and WP calculation, and it also can be said that this system was already reliable toused at The Samaya Ubud Bali Hotel.